Aprendizaje automatico de dinámica de fluidos mediante modelos de datos - Moya Garcia, Beatriz; González, David; Alfaro, Iciar; Chinesta, Francisco; Cueto, Elías (Jornada de Jóvenes Investigadores del I3A, 2019)
Real-time fluid simulation is one of the challenges of credible simulation. Among their applications, simulation-based control of robots manipulating liquids is one of the main research topics. The slosh is of great importance in this field. We suggest a data-driven integrator for the sloshing dynamics able to run in real-time.